Deep-water sediment waves as a special gas hydrate reservoirs in the Northeastern South China Sea. (March 2019) - Bai, Chenyang; Zhang, Guangxue; Lu, Jing'an; Liang, Jinqiang; Yang, Zhen; Yan, Wei; Zhu, Donglin; Tian, Yutang
Abstract: The gas hydrate is attracting increasing attention in the sedimentary geology as an alternative energy source in the future. Recent exploration efforts have indicated that gas hydrate is commonly associated with sediment waves in slope area of quasi-passive continental margin. Based on the deep-water seismic data and core data of the northeastern part of the South China Sea (SCS), this research describes the seismic and geological characteristics of the sediment waves and gas hydrate reservoirs, and discusses the accumulation model of gas hydrate in sediment waves reservoir. The results demonstrate that: (1) the sediment waves widely appear in study area, and those have a "wave-like" bedform and are formed by deep-water contour or turbid current sedimentation. Meanwhile, the sediment waves are affected by gas leakage, diapirism, and neotectonics. (2) The stable zone of gas hydrate which simulated calculation by theory is consistent with core data. The complete and typical gas hydrate seismic model including a "bottom-simulating reflection (BSR) + blank zone (BZ) + enhanced reflector body (eHB)" structure can be observed in the sediment waves seismic profile of the study area. (3) The gas hydrates are stored in sediment waves, which are influenced by the original structure of the sediments and have different gas hydrate accumulation dynamics that are driven by diffusion and/or leakage. Thus, the sediment waves as a favorable reservoir of gas hydrate have research significance. Highlights: This research describes the seismic and geological characteristics of the sediment waves and gas hydrate. This research found that the gas hydrate could accumulate in the sediment waves area. This research provides the gas hydrate has different accumulation dynamic that is driven by diffusion and/or leakage.